2018
DOI: 10.1182/blood-2018-02-830737
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic intercellular redistribution of HIT antigen modulates heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is a prothrombotic disorder initiated by antibodies to platelet factor 4 (PF4)/heparin complexes. PF4 released from platelets binds to surface glycosaminoglycans on hematopoietic and vascular cells that are heterogenous in composition and differ in affinity for PF4. PF4 binds to monocytes with higher affinity than to platelets, and depletion of monocytes exacerbates thrombocytopenia in a murine HIT model. Here we show that the expression of PF4 on platelets and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Third, fibrin accumulation is inhibited by an a-mouse FcRn mAb after vascular injury in a murine model of HIT in which TF is generated in monocytes. 9,41,45 Together, these studies reveal that induction of TF activity requires not only FcgRIIa, as we have previously shown, 42,45 but also FcRn, as we describe here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Third, fibrin accumulation is inhibited by an a-mouse FcRn mAb after vascular injury in a murine model of HIT in which TF is generated in monocytes. 9,41,45 Together, these studies reveal that induction of TF activity requires not only FcgRIIa, as we have previously shown, 42,45 but also FcRn, as we describe here.…”
Section: Discussionsupporting
confidence: 88%
“…Human a-FcRn antibody (SYNT001), mouse a-human PF4/heparin mAb (KKO) or mouse control a-human PF4 monomer mAb (RTO), 40 and mouse a-human FcgRIIa MoAb (clone IV.3) and the corresponding control IgGs (ie, human IgG4 as the negative control for SYNT001 and mouse IgG [TRA] for KKO and for IV.3) were conjugated with Alexa 488, Alexa 568, and Alexa 647 fluorescent dyes, respectively, using antibodylabeling kits (Thermo Fisher, Invitrogen). 41 Cells exposed to HIT ICs or controls were incubated with Alexa 488/SYNT001, Alexa 568/KKO, and Alexa 647/IV.3 mAbs for 1 hour at room temperature. Alexa 488-conjugated human IgG4 and Alexa 568-or Alexa 647-conjugated isotype-matched mouse-irrelevant IgG2b served as the negative controls.…”
Section: Membrane Colocalizationmentioning
confidence: 99%
“…Heparin is a widely used anticoagulant and about 3-5% of patients exposed to heparin can develop a severe drug reaction known as heparin-induced thrombocytopenia (HIT) [1,2]. HIT occurs when antibodies against multimolecular complexes of platelet factor 4 (PF4, CXCL4) and heparin activate platelets and monocytes [3][4][5][6][7][8][9]. PF4 is a tetrameric chemokine with four cysteines, which form two disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to a decrease in monocyte levels is especially noteworthy given that neutrophil counts increased in almost all patients, often dramatically. Recently, Dai et al, 20 reporting on a passive immunization murine model of HIT whereby acute thrombocytopenia was triggered by infusing a HIT-like monoclonal antibody (KKO) to human PF4 (hPF4) þ /FcγIIA receptor (FcγIIA)þ mice, found that acute declines in monocyte levels were observed in mice following an intravenous infusion of KKO (the authors did not report on whether changes in neutrophil counts occurred or not). However, as we also involved a tendency to decreasing monocyte counts in patients with non-HIT thrombosis, the significance if any of mildly declining monocyte levels in our patients with HIT is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 A recent study noted occurrence of transient monocytopaenia in a passive murine immunization HIT model. 20 Other investigators found that HIT antibodies also activate polymorphonuclear leukocytes (neutrophils), leading to leukocyte degranulation. 21 Despite these laboratory studies involving isolated cells and animal models, there is to our knowledge no reported clinical study evaluating changes in leukocyte counts during the clinical course of HIT.…”
Section: Introductionmentioning
confidence: 99%